The 'Generic Competition Paradox' Revisited. Issue 3 (2nd September 2021) - Saha, Atanu; Xu, Yong
Abstract: Using a panel dataset of 78 branded drugs for the period January 2009 through March 2020, we examine whether brand prices react to the onset of generic competition. Contrary to the findings of several prior academic studies, we show that the rate of change of brand prices (both nominal and CPI-deflated) are significantly lower after generics enter the market; notably, we also find branded drug manufacturers raise their prices in the six-month period just before generic entry and lower them in the six-month period after, with the differences in the rates of change being highly significant. We also show in markets with an authorized generic and in ones with large pre-entry brand sales, manufacturers raise prices at a higher (or decrease CPI-deflated prices at a shallower) rate.